Use of session RPE to training load quantification and training intensity distribution in taekwondo athletes - Perandini, L.A.; Siqueira-Pereira, T.A.; Okuno, N. M.; Soares-Caldeira, L. F.; Nakamura, F. Y. (Science & Sports, 2012)
Objective The purposes of this study were to: verify whether rating of perceived exertion (RPE) can be used to determine the training load, using heart rate (HR) and blood lactate concentration ([BLa-]) as the criteria measurements, and determine the association and agreement of training intensity distribution based on RPE and [BLa-] responses in taekwondo training. Methods Eleven elite taekwondo athletes performed a progressive test, in order to estimate maximal HR, and two training sessions. Twenty-two training loads were quantified based on RPE (session-RPE), HR and [BLa-] responses. The training intensity distribution was performed using RPE and [BLa-] responses. The level of statistical significance was set at P < 0.05. Results All correlations between session-RPE with HR and [BLa-] methods were statistically significant (r = 0.52-0.71, P < 0.05). The association between proportions of training intensity distribution based on RPE and [BLa-] responses were significant (P > 0.05) with a high agreement (k = 0.71). Conclusion Taekwondo coaches can use RPE to quantify training loads and training intensity distribution in order to better plan and assist training program.